Pluralismo degli ordinamenti giuridici e le «“nuove” credenze popolari» gramsciane: la sfida della modernità - Lombardi Satriani, Luigi M. (International Gramsci Journal, 2023)
This presentation deals with the importance of Gramsci’s thought for a critical assessment of folklore and its function vis-à-vis hegemonic culture. The contraposition that Gramsci singles out in the conceptions of folklore constitutes a critical nucleus which, for example, would lead anthropological thought in the 1970s to develop the conception of folklore as a culture of contestation, inclusive of the various levels of contestation. This conception animated anthropological debate in those years and the immediately successive decades. One can, moreover, single out in other extracts from Gramsci’s work, considered in its entirety, critical annotations of the greatest interest which are intended, in the new culture that he hoped for, to recover norms and practical rules of conduct having the solidity and imperativeness of traditional popular beliefs. These are aspects which open up the way to a juridical anthropology understood in a modern manner, and are testimony, even in this light, to the innovative approach of the Sard scholar and political activist.